Stereotypies: From Normal to Pathological - Temudo, Teresa; Melo, Cláudia (Journal of Pediatric Neurology, 2015)
Stereotypies are rhythmic, patterned, repetitive, purposeless, and continuous movements which may be categorized into the following two ways: primary, if they appear in healthy normally developing subjects; or secondary, when they are associated with neurologic problems. They may also be divided into motor, vocal, or visual stereotypies. Biological mechanisms of stereotypies are unknown but they seem to be related to the basal ganglia or the cortical-basal ganglia-thalamo-cortical circuits. Stereotypies are frequently found in patients with autistic disorders, intellectual disability, and sensorial deficit disorders. Some neurodevelopmental disorders show specific motor stereotypies, which reinforce the notion of a genetic or neurobiological basis. When necessary, treatment may include behavioral or drug-based approaches.
Keywords: stereotypies; movement disorders; autism